Perception on The Use of Peer Review Technique to Optimizing Students’ Reading Comprehension of Explanation Text in SMAN 1 Surabaya - Muh Rochmat Muchson Santoso; Murni Mahmud; Iskandar (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2024)
The current research looks at the perception of using peer review techniques to improve students' reading comprehension. of explanatory texts at SMAN 1 Surabaya. This study employs a qualitative method approach, utilizing data collected qualitatively from input provided by student and teacher interviews and classroom observations to construct two research issues: (1) In the selected educational context, how to apply the peer review technique to maximize reading comprehension for explanatory texts? (2) How does the peer review approach affect the comprehension of explanatory texts by SMAN 1 Surabaya students when they read them? The findings revealed that specific strategies used by teachers to apply explanatory content to students' understanding of reading, such as encouragement to learn, using electronic media, such as English websites, and preparing other media as support in learning explanatory texts in the use of peer review techniques in reading comprehension students in the classroom. Next, teachers' strategies for using explanatory content in students' reading comprehension include learning motivation, using internet media such as English websites, involving students in group work, organizing the classroom environment for student learning, and preparing other media as support in learning explanatory texts in the use of peer review techniques in reading comprehension.